TEACHER’S STRATEGIES IN TEACHING WRITING RECOUNT TEXT AT SMA NEGERI 1 TEBING TINGGI - Elnita Samosir; Isli Iriani Indiah Pane; Masitowarni Siregar (Universitas Negeri Medan, 2019)
This study was conducted to find out the teacher’s strategies in teaching writing recount text and describe how the strategies applied in teaching writing recount text at SMA Negeri 1 Tebing Tinggi. It used qualitative research design. The subject of this research was one of the English teacher in SMA Negeri 1 Tebing Tinggi. The data of this research were the teacher’s strategies and the activities in teaching writing recount text. The results showed that the teacher applied four strategies from seven strategies by Haynes and Zacarian, they were (1) making lesson visual, (2) modifying vocabulary instruction, (3) using cooperative learning strategy and (4) determining key concepts. Those are the ways how teacher applying the strategies: First, in observing he applied lesson visual strategy. The second, in questioning he modified vocabulary instruction. Third, in experimenting he applied cooperative learning strategy. Finally, he applied determining key concept strategy in associating and communicating stages.Key words: Teaching Writing, Teacher’s Strategies, Recount Text, Qualitative Research.